2014
DOI: 10.1016/j.jalgebra.2014.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Nilpotent Sabinin algebras

Abstract: In this paper we establish several basic properties of nilpotent Sabinin algebras. Namely, we show that nilpotent Sabinin algebras (1) can be integrated to produce nilpotent loops, (2) satisfy an analogue of the Ado theorem, (3) have nilpotent Lie envelopes. We also give a new set of axioms for Sabinin algebras. These axioms reflect the fact that a complementary subspace to a Lie subalgebra in a Lie algebra is a Sabinin algebra. Finally, we note that the non-associative version of the Jennings theorem produces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This is not the standard definition of nilpotency in loops; however, there are strong indications that it is the correct one [18,34,35,39]. Since the commutator-associator filtration is defined in terms of words (namely, commutators, associators and associator deviations and their compositions) nilpotent loops of class n form a variety.…”
Section: Nilpotent Loops and Nilpotent Sabinin Algebrasmentioning
confidence: 99%
See 3 more Smart Citations
“…This is not the standard definition of nilpotency in loops; however, there are strong indications that it is the correct one [18,34,35,39]. Since the commutator-associator filtration is defined in terms of words (namely, commutators, associators and associator deviations and their compositions) nilpotent loops of class n form a variety.…”
Section: Nilpotent Loops and Nilpotent Sabinin Algebrasmentioning
confidence: 99%
“…, X n ) for all n ≥ 2 satisfying the relations ( 9)- (11). It can be shown that if l is a flat Sabinin algebra in this sense, there exists a decomposition (8) which gives rise to the operations on l, [39].…”
Section: Sabinin Algebrasmentioning
confidence: 99%
See 2 more Smart Citations